ANALISIS KEBUTUHAN PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS STUDI KASUS UNTUK PEMBELAJARAN KIMIA - Rizka Fahreza; Retno Dwi Suyanti; Nurfajriani Nurfajriani (PROSIDING SEMINAR KIMIA, 2023)
This study aims to analyze the needs of teachers and students for case study-based chemistry learning media that can support the chemistry learning process for grades X and XI in Senior High Schools (SMTA). The methods used are literature studies (curriculum analysis, analysis of chemical concepts on colloidal topics, and journal analysis) and field studies (analysis of multimedia needs for chemistry teachers and students in class X and XI SMA in the form of a questionnaire using google form to seven high school schools in the district). Coal). Based on the results of the analysis of the first literature study, it was found that the basic competencies regarding colloid systems are KD 3.15 and KD 4.15, then the chemical concepts in colloidal materials are classified as abstract about 17%, abstract concepts with concrete examples show 33%. While the concrete concept of 50%. The results of the journal analysis stated that the development of interactive multimedia based on case studies is important because it can explain abstract concepts to be more concrete. The next stage of the field study showed that 100% of teachers and 91.4% of students stated that it was important to integrate case study-based interactive multimedia content in the learning process. The results of this study provide a clear picture of the need for the development of case study-based interactive multimedia. Keywords: needs analysis, interactive multimedia, case study.